Implicações da apropriação da categoria "agricultura familiar" na trajetória da organização dos agricultores do Alto Uruguai do RS - Everton Lazzaretti Picolotto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2008)
This article aims at to discuss the subject of the potential of the social movements in the renewal of the society starting from the case of the farmers´ movement in the area of Alto Uruguay in the state of Rio Grande do Sul (RS). Based on the assumption that is for best understanding the renovating potential of the movement it becomes necessary to contextualize formerly the process of construction of farmer¿s collective identity revealing its multiple determinations shown. Therefore, they are regarded specifically to the processes of construction of the identity of the "family agriculture", of turning positive this form of agriculture and of the identity differentiation regarding other active movements in the area of Alto Uruguay. Besides, the analysis of this case is particularly enlightener of how a movement of farmers gets to transform its form of social inclusion and the way how it is recognized socially (positively) and to maintain unaffected, at the same time, some practices and conservative conceptions characteristics of the "old colonies of immigrants".